EDUKASI KADER TENTANG GIZI SEIMBANG CALON PENGANTIN SEBAGAI UPAYA PENCEGAHAN STUNTING - Mairo, Queen Khoirun Nisa’; Alfiah, Siti; Sukesi, Sukesi; Kasiati, Kasiati; Munaf, Ade Zakiya Tasman; Sholichah, Agustina Mar’atus; Pipitcahyani, Tatarini Ika; Isfentiani, Dina; Rijanto, Rijanto (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Stunting remains a chronic nutritional problem that affects physical growth, cognitive development, and human resource quality. Prevention efforts should begin during the preconception period through improving nutritional knowledge among prospective brides and grooms. Community health cadres play a strategic role as health educators at the community level. This community service program aimed to enhance cadres’ awareness, commitment, and knowledge regarding balanced nutrition for prospective couples as a strategy to prevent stunting. A community-based participatory approach was employed through interactive education sessions, group discussions, case studies, demonstrations of balanced local food menus, and pre-test and post-test evaluations. A total of 35 health cadres participated in the program. Most participants were aged 31–50 years (57%) and had secondary education (66%). The proportion of cadres with good knowledge increased from 57% in the pre-test to 86% in the post-test. Qualitatively, cadres demonstrated improved awareness, active participation, and commitment to integrating nutrition education into routine posyandu activities and counseling for prospective couples. The program positively strengthened cadres’ capacity as health promotion agents and shows potential sustainability through community empowerment. Preconception nutrition education for cadres is recommended as a promotive and preventive strategy to accelerate stunting reduction at the community level.